Vices of the Learned : Towards a Long-Term History of Scholarly Vices - Hagen, Sjang ten; Paul, Herman (Brill's Studies in Intellectual History, 2026)
Why are professors still warning their students against dogmatism, prejudice, pedantry, and other centuries-old vices? What explains the persistence of these scholarly vices across the ages? With case studies from medieval Europe to twenty-first century America, Vices of the Learned offers a panoramic overview of qualities, habits, and inclinations that scholars at various times and places saw as detrimental to their work. Innovative is the volume's longue durée approach. The volume breaks new ground in highlighting the importance of "low" genres (aphorisms, proverbs, anecdotes) and stereotypical figures (the pedant, the charlatan, the mammon) in transmitting vices over time.